(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The study aimed to identify the risk culture and its impact on the citrus risk management policy in Lattakia. The research community included farmers in the field of citrus cultivation in Lattakia. The questionnaire was distributed to 222 farmers. 210 questionnaires were retrieved and 202 questionnaires were valid for analysis. The results of the study showed that there is a significant effect of the risk culture in the insurance policy, one of the citrus risk management policies in Lattakia, and that there is no significant effect of the risk culture in the risk assumption policy, one of the citrus risk management policies in Lattakia.